2012
DOI: 10.1097/igc.0b013e3182647265
|View full text |Cite
|
Sign up to set email alerts
|

ATL: Results of a Multi-Institutional Phase 2 Study (JGOG1066)

Abstract: Concurrent chemoradiotherapy with HDR-ICBT and standard weekly delivery of cisplatin was feasible with acceptable toxicity in Japanese patients with cervical cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 25 publications
(20 reference statements)
1
10
0
Order By: Relevance
“…32 Discontinuous radiation during radiochemotherapy takes place in 3-20% of the patients. [33][34][35] In the present study the interval took place in 15.7% of the patients, which is within the ranges quoted above.…”
Section: Discussion Of Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…32 Discontinuous radiation during radiochemotherapy takes place in 3-20% of the patients. [33][34][35] In the present study the interval took place in 15.7% of the patients, which is within the ranges quoted above.…”
Section: Discussion Of Resultssupporting
confidence: 69%
“…31 In the groups of patients who underwent radiochemotherapy the treatment time ranges from 35 to 92 days (average time 51-52 days). 32,33 Some researchers point out, however, that prolongation of radiochemotherapy duration, contrary to the prolongation of independent radiotherapy, does not influence the treatment results (recurrence in the radiated area, DFS, OS). 32 Discontinuous radiation during radiochemotherapy takes place in 3-20% of the patients.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a multicenter Phase II trial, the Japanese Gynecologic Oncology Group (JGOG) study 1066 demonstrated that cisplatin-based CCRT using high-dose-rate (HDR) intracavitary brachytherapy (ICBT) achieved comparable outcomes with global dose schedules, despite Japanese centers adopting lower cumulative radiation dose schedules at Point A than those in the USA and Europe [ ]. These centers reported that HDR ICBT was feasible, with acceptable toxicity compared with previous clinical studies of cisplatin-based CCRT [ ]. However, hematologic and renal toxicities, which may lead to treatment delay or dose reduction, remained.…”
Section: Introductionmentioning
confidence: 99%
“…The large tumors volume burden in addition to the advanced stage when presented plus the complication of radioresistant tumors were contributing factors to the ability to achieve effectiveness of radiation therapy. Currently, the new gold standard is concomitant chemoradiation for dealing with locally advanced cervical carcinoma (Thomas., 2000., Green et al, 2001Toita et al, 2012). In addition, The advanced sophisticated radiation techniques such as 3D conformal radiotherapy , intensity modulated radiation therapy (IMRT) along with advanced imaging applications have increased in usage for locally advanced cervival cancer (Petsuksiri et al, 2012).…”
Section: Introductionmentioning
confidence: 99%